Determination of the most effective WiFi signal intensity area in an enclosed room - Zamri Zamri; Yan Soerbakti (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2022)
WiFi signal is an electromagnetic wave that in its transmission does not require an intermediary medium used in communication. However, signal intensity can be affected by the medium through which it travels, as is the case in the workplace. So the WiFi signal no longer provides the same strong intensity. Therefore, it is necessary to research how to determine the area with the most effective WiFi signal intensity due to fluctuating signal propagation in a closed workspace. This research is conducted by showing the source point of the router and receiver that will be used as a trip to the position function, then measurements will be made on the WiFi signal depending on the change in position. In addition, the influence of temperature and humidity in the room is also related. The results showed that the highest WiFi signal intensity was at a distance of 0.5 m from the router with a power loss of -47 dBm. While the value of the lowest WiFi signal intensity is in the range of 3 m with a power loss of -25 dBm.